فعالية برنامج تدريبي قائم على الكفاءة الذاتية في خفض الأفكار اللاعقلانية لدى طلاب المرحلة الإعدادية - حنا، ميرنا مكرم عدلي; رمضان، أحمد ثابت فضل (جامعة مدينة السادات - كلية التربية, 2024)
هدف البحث إلى تقصي فعالية برنامج تدريبي قائم على الكفاءة الذاتية في خفض الأفكار اللاعقلانية لدى طلاب المرحلة الإعدادية، ولتحقيق هدف البرنامج استخدمت الباحثة المنهج التجريبي ذو المجموعتين التجريبية والضابطة على عينة من طلاب المرحلة الإعدادية بإدارة أشمون التعليمية بمحافظة المنوفية وعددهم (٦٠ طالبا وطالبة) تراوح العمري الزمني لهم بين (۱۲ إلى ١٤ سنة) بمتوسط عمري (۱۳٫۱ سنة) وانحراف معياري (٠,٨٥) وتم تقسيمهم إلى مجموعتين متساويتين لكل منهما (۳۰ طالبا وطالبة) تم تطبيق البرنامج التدريبي على المجموعة التجريبية فقط، كما أعدت الباحثة أدوات الدراسة والتي تمثلت في (مقياس الأفكار اللاعقلانية- البرنامج القائم على الكفاءة الذاتية) وقد تم تطبيق أدوات الدراسة عليهم، وتوصلت الدراسة إلى وجود فروق بين المجموعتين التجريبية والضابطة في القياس البعدي لمقياس الأفكار اللاعقلانية لصالح المجموعة التجريبية، كما أن هناك فروقا بين القياسين القبلي والبعدي للأفكار اللاعقلانية والمرونة النفسية لدى طلاب المجموعة التجريبية، كما تم التوصل إلى استمرار فعالية البرنامج التدريبي القائم على الكفاءة الذاتية في خفض الأفكار اللاعقلانية لدى طلاب المجموعة التجريبية بعد مرور شهرين من انتهاء التدريب. The research aimed to investigate the effectiveness of a training program based on self-efficacy in reducing irrational thoughts among middle school students. To achieve the goal of the program, the researcher used the experimental method with two experimental and control groups on a sample of middle school students in the Ashmoun Educational Administration in Menoufia Governorate. They numbered (60 male and female students), ranging in age. The time period for them was between (12 to 14 years) with an average age of (13.1 years) and a standard deviation of (0.85). They were divided into two equal groups each (30 male and female students). The training program was applied to the experimental group only. The researcher also prepared the study tools, which were (The Irrational Thoughts Scale - the program based on self efficacy) and the study tools were applied to them. The study found that there were differences between the experimental and control groups in the post measurement of the Irrational Thoughts Scale in favor of the experimental group. There are also differences between the pre- and post-measurements of irrational thoughts and psychological flexibility among students. The experimental group. It was also found that the effectiveness of the training program based on self-efficacy continued to reduce irrational thoughts among the students of the experimental group two months after the end of the training.
Keywords: الصحة النفسية -- السلوكيات السلبية -- التفكير العقلاني -- طلبة المدارس